Assessing the barriers to image‐guided drug delivery. (31st October 2013) - Lanza, Gregory M.; Moonen, Chrit; Baker, James R.; Chang, Esther; Cheng, Zheng; Grodzinski, Piotr; Ferrara, Katherine; Hynynen, Kullervo; Kelloff, Gary; Lee, Yong‐Eun Koo; Patri, Anil K.; Sept, David; et al.
Abstract : Imaging has become a cornerstone for medical diagnosis and the guidance of patient management. A new field called image‐guided drug delivery (IGDD) now combines the vast potential of the radiological sciences with the delivery of treatment and promises to fulfill the vision of personalized medicine. Whether imaging is used to deliver focused energy to drug‐laden particles for enhanced, local drug release around tumors, or it is invoked in the context of nanoparticle‐based agents to quantify distinctive biomarkers that could risk stratify patients for improved targeted drug delivery efficiency, the overarching goal of IGDD is to use imaging to maximize effective therapy in diseased tissues and to minimize systemic drug exposure in order to reduce toxicities. Over the last several years, innumerable reports and reviews covering the gamut of IGDD technologies have been published, but inadequate attention has been directed toward identifying and addressing the barriers limiting clinical translation. In this consensus opinion, the opportunities and challenges impacting the clinical realization of IGDD‐based personalized medicine were discussed as a panel and recommendations were proffered to accelerate the field forward. WIREs Nanomed Nanobiotechnol 2014, 6:1–14. doi: 10.1002/wnan.1247 This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease